Developing Electroluminescent Devices Using R2R - Guilera Grandes, Núria; Vilar Abril, Laia; Álvarez de Lasarte Sagrera, Irene (Ingeniería Solidaria, 2014)
Electroluminescent (EL) devices are a perfect example of solid state lighting. These devices have been produced using flat roll-to-roll screen printing in a total of four layers, one on top of another, making 200 devices a day. el devices have been subjected to extreme conditions in environmental chambers at 40 .C and 90% relative humidity for up to 336 hours, applying a voltage of 150 V and 750 Hz. The protection of electroluminescent devices against humidity and temperature was investigated, and it was found that the films tested offer less protection than silicon inks, as these provide greater system flexibility as well as greater resistance to humidity and temperature.
Keywords: electroluminescent; encapsulation; inorganic; roll-to-roll; fabric